A Design of Fractal Hilbert MIMO Antenna for 5G Mobile - Noora Rafid Kamil; Ahmed Ghanim Waddy; Aseel Hameed AL-Nakkash (Journal of Techniques)
This paper presented two new fractal Hilbert MIMO antenna designs with different two thicknesses (0.8mm and 1 mm) and used hybrid techniques between neutralization lines (NL) and defected ground structure (DGS), to enhance mutual coupling of the antenna for 5G applications. Higher isolation and smaller size are major advantages of this design.  ​The proposed fractal Habrit curve MIMO antennas were fabricated for the 3800 - 5460 MHz and 3735-5390 MHz bands with a 49 dB and 40 dB return loss and high isolation of 19.67 dB and 18.5 dB, using FR4 with dimensions of (24 × 45 × 0.8mm3) and (24 × 45 × 1mm3) respectively. The results prove that the MIMO antenna is suitable for a sub-6 band that is qualified for 5G smartphone applications.